Resting-State fMRI in Predicting Response to Treatment With SSRIs in First-Episode, Drug-Naive Patients With Major Depressive Disorder - Zhang, Aixia; Wang, Xin; Li, Jianying; Jing, Lin; Hu, Xiaodong; Li, Hejun; Yang, Chunxia; Zhang, Kerang; Sun, Ning (Frontiers in Neuroscience, 2022)
Objective: Depression (DD) lacks neuroimaging markers of pharmacological treatment efficacy. We studied the neuroimaging mechanisms of patients with first-episode DD and explored markers that predict the efficacy of SSRIs based on resting-state brain imaging technology. Methods: 101 patients with first-episode DD and 53 normal controls were included. Based on the reduction rate from before to after 2 weeks of SSRI drug treatment, 31 patients were placed in the ineffective group, and 32 patients were placed in the effective group. Compare differences in brain function between the DD and normal control groups, and the diagnostic value of brain function regarding DD was analyzed. Differences in brain function between the DD and normal control groups were used as a mask, and the differences in brain function between the effective and ineffective groups were compared. Correlations between the differences in brain function between the effective and ineffective groups and the HAMD-17 reduction rate from before to after 2 weeks of SSRI drug treatment were analyzed. Results: In the DD group relative to the normal control group increased ReHo was seen in the left parahippocampal gyrus and right parahippocampal gyrus; decreased ReHo was seen in the right middle occipital gyrus; decreased functional connectivity was observed in the right and left parahippocampal gyrus, right middle occipital gyrus and middle temporal gyrus. ROC curve analysis showed that the AUC for ReHo was 0.544 (95% CI=0.445-0.644), and the AUC was 0.822 (95% CI=0.734-0.909) for functional connectivity. Logistic regression pooling of the differences in ReHo mean time series with the functional connectivity mean time series was performed for the ROC curve analysis, and the AUC was 0.832 (95% CI=0.752-0.911). Relative to the effective group, the invalid group elevated ReHo was seen in the right parahippocampal gyrus, and lower functional connectivity was found in the middle temporal gyrus. ReHo values were negatively correlated with HAMD-17 score reductions after 2 weeks of SSRI medication. Conclusion: Abnormalities in resting-state brain function may be a biological marker for the diagnosis of DD. ReHo values are expected to be predictors of the efficacy of SSRI drug treatment.